171 RECOMBINANT HUMAN VEGF TREATMENT ENHANCES ALVEOLARIZATION AFTER HYPEROXIC LUNG INJURY IN NEONATAL RATS. (1st January 2005) - Kunig, A.; Balasubramaniam, V.; Markham, N.; Morgan, D.; Montgomery, G.; Grover, T.; Abman, S.
Abstract : Background: BPD is characterized by decreased alveolarization and dysmorphic vascular growth. Although growth of the pulmonary circulation and alveolarization are closely coordinated, mechanisms that link alveolar and vascular growth are poorly understood. Clinical studies suggest that VEGF, a potent endothelial cell mitogen and survival factor that promotes angiogenesis, is decreased in lungs of infants who died with BPD. Past studies in rats have shown that neonatal exposure to prolonged hyperoxia inhibits lung growth and down-regulates lung VEGF expression. Recent studies have shown that neonatal treatment with a VEGF receptor inhibitor decreases vascular and alveolar growth. Overall, these findings suggest that impaired VEGF signaling may contribute to decreased lung growth in BPD. Whether chronic treatment with exogenous VEGF improves lung structure in experimental models of BPD is unknown. Hypothesis/Objectives: The purpose of this study was to determine whether prolonged VEGF treatment would enhance alveolarization in infant rats after exposure to neonatal hyperoxia. Methods: Two day old SDR pups were placed into hyperoxia (FiO2, 0.75) or room air for 12 days. At 14 days, pups were randomized to daily treatment with rhVEGF 165 at 20 μg/kg im or vehicle (saline; controls). On day 22, rats were killed, and the heart and lungs were collected for study. Morphometric analysis was assessed by radial alveolar counts (RAC), mean linear intercepts (MLI), and skeletonization. Results: In comparison with room air controls, hyperoxia decreased RAC (6 ± 2 vs. 11 ± 2; p ≤ 0.01), increased MLI (59 ± 10 vs. 44 ± 4; p ≤ 0.01), decreased the number of nodal points per high power field (503 ± 12 vs. 447 ± 14; p≤0.01), and decreased vessel density (19 ± 1 vs. 12 ± 1; p≤0.01) despite recovery in room air. In comparison with hyperoxic controls, rhVEGF treatment after hyperoxia increased RAC (12 ± 2; p≤ 0.01), decreased MLI (42 ± 6; p ≤ 0.01 vs. hyperoxia), increased nodal point density (502 ± 7; p≤0.01), and increased vessel density (23 ± 0.4; p≤0.01). Conclusions: We conclude that exposure of neonatal rats to hyperoxia impairs alveolarization, which persists despite recovery in room air, and that treatment with rhVEGF during the recovery period enhanced alveolarization. We speculate that persistent abnormalities of lung structure after hyperoxia may be partly due to impaired VEGF signaling, and that increased alveolarization after VEGF treatment may be due to improved endothelial cell survival, function and growth.